Translating Quechua Multilingualism and European Multilingual Intertextuality in the Short Stories of Edgardo Rivera Martínez - Amy Olen (Studies in 20th & 21st Century Literature, 2024)
Quechua multilingualism is a significant feature of Andean literature written in Spanish, playing a key role as a marker of Indigeneity interacting with mestizo culture and the Spanish language. In the short stories of Peruvian author Edgardo Rivera Martínez (1933-2018), a mestizo, non-Indigenous writer, Quechua multilingualism is conveyed in different forms and has different functions. It interacts with European-language multilingual intertextuality to portray the tensions and convergences of languages and cultures in the Peruvian Central Andes. When tasked with translating Rivera Martínez’s multilingual short stories from Spanish to English, key questions arise, including the ways Quechua, as a multilingual element the author’s texts, interacts with Spanish and other European languages; what the different multilingualisms convey; and how we might render them into English for a diverse readership. In this essay, I discuss Quechua multilingualism and European multilingual intertextuality in Rivera Martínez’s narrative, and the translation approaches he uses to craft his stories in Spanish. I turn to translation approaches to rendering multilingualism in his work in English translation and suggest that reading and translating his fiction must consider the work Quechua multilingualism performs as an expression of Andean Indigeneity in Spanish-language Andean literature.
Keywords: Andean literature; Quechua; Multilingualism; Translation; Coloniality of Language